Short- and Mid-Term Impacts of COVID-19 Outbreak on the Nutritional Quality and Environmental Impact of Diet - Marty, Lucile; de Lauzon-Guillain, Blandine; Nicklaus, Sophie (Frontiers in Nutrition, 2022)
Background: Changes in dietary behaviours that occurred at the beginning of the COVID-19 outbreak and in particular during the first national lockdowns have been extensively studied across countries. Beyond the understanding of contextual changes in diets due to a temporary lockdown, it is of interest to study longer term consequences of the COVID-19 outbreak as sustained changes in diets may have both an impact on population health and the environment. Objectives: This study aimed to examine both short-term (after one month) and mid-term (after one year) impacts of the COVID-19 outbreak on the nutritional quality and environmental impact of diets, and as a secondary objective on food choice motives. Methods: We analysed dietary data and importance of nine food choice motives recorded through online questionnaires before, during and 1 year after the first lockdown for 524 French participants. Adherence to the French dietary recommendations was estimated using the simplified PNNS-GS2, scoring from −17 to 11.5. Environmental impact was assessed by calculating greenhouse gas emissions in CO2eq/2000 kcal. Results: We analysed dietary data recorded before, during and 1 year after the first lockdown for 524 French participants. We showed a short-term decrease in nutritional quality (-0.26 points on sPNNS-GS2, p = 0.017) and environmental impact (-0.17 kg CO2eq/2000 kcal, p = 0.004) but this decrease was only temporary and nutritional quality (-0.01 points on sPNNS-GS2, p = 0.974) and environmental impact (-0.04 kg CO2eq/2000 kcal, p = 0.472) were not different from their initial values one year later. Some of the food choice motives followed the same trend of a short-term increase and a mid-term stability (health, natural content, ethical concern and weight control). On the contrary, we showed both short-term and mid-term decrease in convenience, familiarity and price motives. Conclusion: Changes in diets and motives observed during the first lockdown were mostly temporary. However, we highlighted a sustained decrease in perceived constraints due to food shopping and food preparation which highlights a positive trend towards more pleasure associated to cooking time.